Effect of exercise intensity on redox biomarkers in healthy adults: A systematic review and meta-analysis of randomized clinical trials - Flor Isela Torres-Rojo; Liliana Aracely Enríquez-del Castillo; Susana Aidée González-Chávez; Luis Alberto Flores-Olivares; Estefanía Quintana-Mendias; Claudia Esther Carrasco-Legleu (PLoS ONE, 2025)
Purpose This meta-analysis aimed to establish the effect of vigorous and non-vigorous exercise interventions on biomarkers of redox status in healthy adults. Materials and methods Based on the PRISMA guidelines, we searched the following databases: Scopus, Web of Science, PubMed, Springer, Science Direct, Cochrane Library, Dialnet, Redalyc, and Lilacs for randomized controlled clinical trials investigating the effect of non-vigorous and vigorous chronic exercise in healthy adults, with the evaluation of antioxidants. The quality of evidence and risk of biases were assessed using the PEDro scale and version 2 of the Cochrane tool for risk of bias assessment in randomized trials (RoB2). Results Seven randomized clinical trials evaluating nine training protocols were included (n=267). Individual evaluations demonstrated an increase in antioxidant capacity (I2=0%, Z=4.56, p<0.00001) and superoxide dismutase (I2=52%, Z=1.94, p=0.05), an antioxidant enzyme, and decrease in pro-oxidant (I2=0%, Z=5.91, p<0.0001); there was no significant difference in glutathione peroxidase (I2=81%, Z=0.50, p=0.62). The effect of vigorous interventions showed an increase in antioxidants (Z=2.44, I2=67%, p=0.01) and a decrease in oxidants (Z=5.44, I2=0%, p<0.00001), while in non-vigorous exercise, no significant differences were observed in redox status. Conclusions The vigorous physical exercise presented better results on antioxidant and oxidative capacity compared to non-vigorous intensity training protocols in healthy people. Finding the optimal balance between exercise intensity and oxidative stress is crucial for maximizing the production of antioxidant enzymes, which can enhance physiological function and increase resistance to OS.